The Deficit of Early Selective Attention in Adults With Sluggish Cognitive Tempo: In Comparison With Those With Attention-Deficit/Hyperactivity Disorder - Park, Yelin; Lee, Jang-Han (Frontiers in Psychology, 2021)
Sluggish cognitive tempo (SCT) is a cluster of attentional symptoms characterized by being slow in behavior and information processing, distractibility, mental confusion, absent-mindedness and hypoactivity. The present study aimed to compare the early and late selective attention in the information processing speed of adults with SCT to those with attention-deficit/hyperactivity disorder (ADHD) and adults without any attentional problems. The participants were divided into the following groups screened by Barkley Adult ADHD Rating Scale-IV: SCT (N = 24), ADHD (N = 24), and healthy controls (N = 25). All participants completed the irrelevant distractor task measuring early and late selective attention under load condition (low vs. high) and distractor condition (no-distractor vs. distractor). The inefficiency index was calculated by RT of distractor condition subtracted by RT of no-distractor condition of correct trials to control the impact of accuracy. The results showed that the SCT group showed a lower efficiency compared to the ADHD group under high load. In addition, the ADHD group showed lower efficiency under low load than high load. It means that the ADHD group have increased the efficiency of selective attention with higher load, while SCT group have low efficiency of selective attention even under high loads. These results suggest that the symptoms of ‘slow’ or ‘distracted’ shown in SCT could be attributable to the reduced speed and efficiency of selective attention in early information processing process and the problem can be pronounced in situations with distractors. The results of the study imply that the attention-deficit-like symptoms shown in those with SCT and ADHD can be distinguished in specific stage of information processing process.